GE_GERICHTE P/9135/2016 vom 22. Juni 2021 - GE Cour de justice (2021)
VOL(DROIT PÉNAL);VIOLATION DE DOMICILE;DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);RESPONSABILITÉ RESTREINTE(DROIT PÉNAL);DIRECTIVE(INJONCTION) | CP.186 CP; CP.19.al2; CP.139; CP.144; CP.44.al2